Structural characteristics of immunogenic liver-stage antigens derived from P. falciparum malarial proteins (2009)
A fully effective antimalarial vaccine must contain multiple proteins from the different development stages of Plasmodium falciparum parasites involved in host-cell invasion or their biologically active fragments. It must therefore include sporozoite molecules able to induce protective immunity by blocking the parasite's access to hepatic cells, and/or proteins involved in the development of this stage, amongst which are included the Liver Stage Antigen-1 (LSA-1) and the Sporozoite and Liver Stage Antigen (SALSA). Our studies have focused on the search for an association between the structure of high activity binding peptides (HABPs), including both conserved native and their modified analogues, and their ability to bind to the MHC Class II HLA-DR molecules during formation of the MHCII-peptide-TCR complex leading to inducing the appropriate immune response. These studies are part of a logical and rational strategy for developing multi-stage, multi-component, minimal subunit-based vaccines, mainly against the P. falciparum malaria. © 2009 Elsevier Inc. All rights reserved.